Impact of comorbidity on health outcome after a transport-related injury. Issue 3 (19th April 2019) - Samoborec, Stella; Simpson, Pamela; Hassani-Mahmooei, Behrooz; Ruseckaite, Rasa; Giummarra, Melita; Ayton, Darshini; Evans, Sue
Abstract : Introduction: Understanding the impact of comorbidity on health outcomes is important given that comorbidities can affect survival, morbidity, service delivery costs and healthcare utilisation. However, little is known about the types of comorbidities affecting specific health outcomes after minor to moderate road trauma. Methods: This study involved 1574 participants who claimed injury compensation following transport-related injury. Cross sectional data were collected. Health outcomes were assessed using the EQ-5D-3L specific domains and summary score. Twelve self-reported pre-existing chronic conditions were assessed using a multivariate logistic regression, adjusting for demographic and injury characteristics. Results: Out of 1574 participants, only 17 (1%) participants reported no pre-existing comorbidities, 72% reported one, 13% reported two and 14% reported three or more comorbidities. Hypertension (15%), depression (14%) and anxiety (14%) were the most commonly reported comorbidities, followed by arthritis (13%), chronic pain (11%) and asthma (11%). Participants with a history of arthritis (adjusted odds ratio [AOR] 1.90, 95% CI 1.24 to 2.91); chronic back pain (AOR 1.59, 95% CI, 1.04 to 2.43); other chronic pain (AOR 2.73, 95% CI 1.42 to 4.24); depression (AOR 2.55, 95% CI 1.60 to 4.05) and anxiety (AOR 2.08, 95% CI 1.32 to 3.26) were at increased risk of poorer health outcomes, after controlling for age, gender, type of injury and time since injury. Conclusion: This study found that comorbidities such as arthritis, chronic back pain, other chronic pain, depression and anxiety significantly increase the odds of poorer health postinjury, regardless of the time since injury. Regular screening of comorbid conditions may help identify people likely to have poorer outcomes, thereby enabling the implementation of interventions to optimise health despite the presence of comorbidities.